An optimized agonist peptide of protease-activated receptor 4 and its use in a validated platelet-aggregation assay. (3rd October 2022) - Yang, Jing; Mapelli, Claudio; Wang, Zhaoqing; Sum, Chi Shing; Hua, Ji; Lawrence, R. Michael; Ni, Yan; Seiffert, Dietmar A.
Abstract: Protease-activated receptor 4 (PAR4) is a promising drug target to improve the efficacy/safety window of antiplatelet agents. The native peptide GYPGQV, and the more-potent peptide AYPGKF, are PAR4-specific activators. However, these PAR4 agonist peptides (APs) elicit an agonist response, for example, platelet aggregation, at concentrations of 50 to 1000 µM in platelet-function assays, thereby limiting their utility to monitor the pharmacodynamic effects of PAR4 antagonists over a wide concentration range. Improved pharmacodynamic assays are needed for clinical development of PAR4 antagonists. We attempted to identify potent PAR4 APs to aid development of robust assays for optimization of PAR4 antagonists. Using an AYPG-based biased phage-display peptide library approach followed by chemical peptide optimization, A-Phe(4-F)-PGWLVKNG was identified. This peptide demonstrated an EC50 value of 3.4 µM in a platelet-aggregation assay, which is 16-fold more potent than AYPGKF. Using this new PAR4 AP, a platelet-rich plasma-aggregation assay using light-transmission aggregometry was developed and validated in a series of precision and reproducibility tests. PAR4 antagonist responses to PAR4 AP A-Phe(4-F)-PGWLVKNG (12.5 µM to 100 µM) were subsequently evaluated in this assay in vitro and ex vivo in a human study using BMS-986120, a PAR4 antagonist that entered clinical studies.